Optical spectroscopic methods for probing the conformational stability of immobilised enzymes - Ganesan, A.; Moore, B.D.; Kelly, S.M.; Price, N.C.; Rolinski, O.J.; Birch, D.J.S.; Dunkin, I.R.; Halling, P.J. (ChemPhysChem, 2009)
Structure of immobilised enzymes : Circular dichroism, infrared and fluorescence spectroscopic methods are used to characterise in situ structural stability of enzymes immobilised on particles. The enzyme subtilisin Carlsberg exhibits a similar secondary structure in solution and in the immobilised state but on the surface of porous silica gel a rigid tertiary structure is preferred. We report the development of biophysical techniques based on circular dichroism (CD), diffuse reflectance infrared Fourier transform (DRIFT) and tryptophan (Trp) fluorescence to investigate in situ the structure of enzymes immobilised on solid particles. Their applicability is demonstrated using subtilisin Carlsberg (SC) immobilised on silica gel and Candida antartica lipase B immobilised on Lewatit VP.OC 1600 (Novozyme 435). SC shows nearly identical secondary structure in solution and in the immobilised state as evident from far UV CD spectra and amide I vibration bands. Increased near UV CD intensity and reduced Trp fluorescence suggest a more rigid tertiary structure on the silica surface. After immobilised SC is inactivated, these techniques reveal: a) almost complete loss of near UV CD signal, suggesting loss of tertiary structure; b) a shift in the amide I vibrational band from 1658 cm -1 to 1632 cm -1 , indicating a shift from α-helical structure to β-sheet; c) a substantial blue shift and reduced dichroism in the far UV CD, supporting a shift to β-sheet structure; d) strong increase in Trp fluorescence intensity, which reflects reduced intramolecular quenching with loss of tertiary structure; and e) major change in fluorescence lifetime distribution, confirming a substantial change in Trp environment. DRIFT measurements suggest that pressing KBr discs may perturb protein structure. With the enzyme on organic polymer it was possible to obtain near UV CD spectra free of interference by the carrier material. However, far UV CD, DRIFT and fluorescence measurements showed strong signals from the organic support. In conclusion, ...